What is the general Welfare: Welfare economic perspectives on equity - Charles F. Manski (Proceedings of the National Academy of Sciences, 2026)
Researchers cannot definitely interpret what the framers of the United States Constitution intended when they wrote of the “general Welfare.” Nevertheless, researchers can conjecture by specifying social welfare functions that aim to express the preferences of the population. An extensive literature in welfare economics addresses the matter. Nevertheless, economists have often simplified policy analysis by assuming that individuals have homogeneous, consequentialist, and self-centered preferences. Individuals may hold heterogeneous private and distributional preferences. To enhance policy analysis, economists should specify social welfare functions that express the richness and variety of actual personal preferences. The possibilities are vast. I focus on preferences for equity. There has been much controversy regarding interpretation of equity, a term that public discourse has used in vague and conflicting ways. Specifying social welfare functions that formally express different interpretations of equity will not eliminate disagreements, but it should clarify concepts and reduce the inconsistencies that afflict verbal communication.